Smart sun tracking with automated cleaning system for PV modules - Amirah Afiqah, Ahmed (2012)
Solar power is one of environment friendly power source. It is characterized by being highly dependent on the radiation level which is function of sun position at the sky. As it is a single axis tracker, the tracker will follows the Sun‟s in East-West movement. While, a smart sun tracking is a system develop to make sure that the PV module always perpendicular to the sun for maximum extraction. To control the single axis rotation, the circuit is programmed to fulfill a minimum and maximum requirement value from the PV module. When the amount of radiation on the module is not between the required values, power window motor will rotate until it reaches a point where the produces voltage is acceptable. As for cleaning purposes, a mechanism consists of sliding brushes has been developed. The mechanism works with the help of gravity which when the module inclined, the brushes will slide to the same direction of the module and clean the module surface. The automated cleaning system is implemented to prevent the formation of dust on the module surface. It is to make sure that the module can extract maximum capacity of solar power.